West of Slavery : The Southern Dream of a Transcontinental Empire - Waite, Kevin (Historian) (Book collections on Project MUSE., 2021)
"When American slaveholders looked west in the mid-nineteenth century, they saw an empire unfolding before them. They pursued that vision through war, diplomacy, political patronage, and perhaps most effectively, the power of migration. By the eve of the Civil War, slaveholders and their allies had transformed the southwestern quarter of the nation--California, New Mexico, Arizona, and parts of Utah--into an appendage of the South's plantation states. Across this vast swath of the map, white Southerners extended the institution of African American chattel slavery while also defending systems of Native American bondage. This surprising history uncovers the Old South in unexpected places, far west of the cotton fields and sugar plantations that exemplify the region"--